Surgically shaping children : technology, ethics, and the pursuit of normality - Parens, Erik, 1957- (UPCC book collections on Project MUSE., 2006)
"At a time when medical technologies make it ever easier to enhance our minds and bodies, a debate has arisen about whether such efforts promote a process of 'normalization,' which makes it ever harder to tolerate the natural anatomical differences among us. The debate becomes especially complicated when it addresses the surgical alteration, or 'shaping,' of children. This volume explores the ethical and social issues raised by the recent proliferation of surgeries designed to make children born with physical differences look more normal. Using three cases--surgeries to eliminate craniofacial abnormalities such as cleft lip and palate, surgeries to correct ambiguous genitalia, and surgeries to lengthen the limbs of children born with dwarfism--the contributors consider the tensions parents experience when making such life-altering decisions on behalf of or with their children. The essays in this volume offer in-depth examinations of the significance and limits of surgical alteration through personal narratives, theoretical reflections, and concrete suggestions about how to improve the decision-making process. Written from the perspectives of affected children and their parents, health care providers, and leading scholars in philosophy, sociology, history, law, and medicine, this collection provides an integrated and comprehensive foundation from which to consider a complex and controversial issue. It takes the reader on a journey from reflections on the particulars of current medical practices to reflections on one of the deepest and most complex of human desires: the desire for normality." --